Female cycling movement: How to construct biomechanical digital-twins - Verwulgen, S.; Danckaers, F.; Audenaert, E.; Duquesne, K.; Steenackers, G.; Ribbens, B.; Sijbers, J.; Verwulgen, S. (Journal of Science and Cycling, 2024)
Cycling witnesses an increasing number of women breaking barriers and inspiring change. Despite these advancements, there remains significant work to achieve full equality and recognition for women cyclists. Key gender gaps persist in: